2012
DOI: 10.1039/c2ra22213b
|View full text |Cite
|
Sign up to set email alerts
|

Palladium catalysed regioselective arylation of indoles, benzofuran and benzothiophene with aryldiazonium salts

Abstract: Aryldiazonium tetrafluoroborates have been successfully employed in the direct and regioselective arylation of heteroaromatics such as indole, benzofuran and benzothiophene. The cationic aryl palladium intermediates derived from the aryldiazonium salts act as effective electrophiles in the process. These arylating reactions display operational simplicity and provide the arylated heterocycles regioselectively in moderate to excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
35
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 30 publications
1
35
0
3
Order By: Relevance
“…Hypervalent iodine derivatives [9], aryltriflates [10][11][12], or aryltosylates [13] have also been employed successfully. Arenediazonium salts have also been used as aryl sources through palladium-catalyzed non-radical direct C-H arylations of heterocycles [14,15]. However, the couplings with such arylating agents still suffer of limitations in terms of regioselectivity for some of these couplings and also to the limited functional group tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…Hypervalent iodine derivatives [9], aryltriflates [10][11][12], or aryltosylates [13] have also been employed successfully. Arenediazonium salts have also been used as aryl sources through palladium-catalyzed non-radical direct C-H arylations of heterocycles [14,15]. However, the couplings with such arylating agents still suffer of limitations in terms of regioselectivity for some of these couplings and also to the limited functional group tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that in the transition metal catalyzed direct C-H bond functionalization of heteroaromatic compounds, additives are usually proposed to enhance the reactions to some extent. Therefore, a series of copper salts was first examined, and it was found that copper salts can indeed affect the reaction (Table 1, entries [8][9][10][11][12][13][14]. For example, all copper salts besides CuBr can promote this reaction to give higher yields, and the best result was achieved using Cu 2 O as the additive (Table 1, entry 11).…”
mentioning
confidence: 99%
“…Allerdings muss Schema 1. [14] Allerdings sind die Nachteile dieser Ansätze ähnlich wie bei der C2-Arylierung. [2][3][4] Schema 2.…”
unclassified
“…Allgemeine Strategien fürKreuzkupplungsprodukte von Phenolen mit Benzo[b]thiophenen und Konzept dieser Arbeit. [8][9][10] [*] S. Lips [12] oder Nheterocyclischen Carbenen [13] ( [14] Allerdings sind die Nachteile dieser Ansätze ähnlich wie bei der C2-Arylierung. Zusätzlich sind mehrere komplexe mehrstufige Verfahren bekannt.…”
unclassified